Estimation of Idle Emissions from the On-Road Vehicles in Dhaka - Rana, M. M.; Khan, M. H.; Azad, M. A. K.; Rahman, S.; Kabir, S. A. (Journal of Scientific Research, 2020)
Vehicle emission is a major source of air pollution in Dhaka. Old fleet, lack of maintenance, improper traffic and parking management, overloading, fuel adulteration etc. are responsible for high emissions from the vehicle sector. In this study, vehicle emissions have been measured on-road in Dhaka using an Automotive Gas Analyzer and Smoke Opacity Meter to determine the existing vehicle emission scenario in the city. Concentrations of carbon monoxide (CO) and hydrocarbons (HC) in the emissions from CNG/gasoline vehicles, and opacity of the emissions from diesel vehicles were measured. The results were compared with the corresponding national limit values. It was found that all types of CNG vehicles performed very well with more than 80% satisfying the corresponding limit values. Private cars ranked at the top in performance among the CNG/gasoline vehicles. Diesel vehicles were found as the worst polluters in the vehicle sector; emissions from about 75% of the diesel vehicles had opacity more than 65 HSU, the national limit value for emissions from diesel vehicles. Motor cycles were also highly polluting; 60% of the motor cycles emitted CO and HC concentrations higher than the respective national emission limit values.